DAMPAK KONSUMSI KOPI ARABIKA ESPRESSO DALAM MENURUNKAN KADAR GLUKOSA DARAH PADA PASIEN DIABETES MELITUS TIPE 2 - Dhigna Luthfiyani Citra Pradana; Aprilla Ayu Wulandari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Diabetes mellitus patients in 2013 had 382 millions people in the world dan approximately increase to 592 millions people who suffered diabetes mellitus in 2035. Consuming coffee can reduce risk factor of diabetes mellitus trough improving hyperglycemia in diabetes-induced mice. Coffee of Arabica Aceh Gayo is a original plant of Aceh Indonesia can consumed of people with processing coffee beans as a drink. Clinical Research of patients of diabetes mellitus type 2 who consume coffee Arabica espresso and patients of diabetes mellitus type 2 do not consume coffee Arabica espresso. The objective of research know to affected decreasing blood glucose from clinical data of fasting blood glucose. The clinical research of quasi experimental of after and before with control design. Total population of diabetes mellitus type 2 patients at UPN Veteran Jakarta in age 30-60 years old amount to 10 people divided 5 people for intervention group and 5 people for control group. Based on the research results have significant different among patient of diabetes mellitus type 2 who consume coffee and patient of diabetes mellitus type 2 with placebo.